ON THE ISSUE OF CHOOSING TACTICS FOR MANAGING WOMEN WITH MENORRHAGIA ASSOCIATED WITH UTERINE LEIOMYOMA - Bekbauliyeva, G.N.; Dusmatova , D.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Summary. The dishormonal nature of uterine leiomyoma defines the main direction of pharmacological treatment — the use of drugs that reduce ovarian estrogen production and exert an antiproliferative effect on endometrial tissue. The use of purely progestogenic agents to correct hormonal imbalance in women with uterine leiomyoma who have not yet fulfilled their reproductive plans is considered the most promising approach, due to their positive impact on both the uterus and hemostasis. Therefore, the need for an individualized therapeutic approach remains relevant. The aim of the study was to determine an individualized treatment strategy for menorrhagia caused by uterine leiomyoma. Sixty patients aged 28 to 45 years with abnormal uterine bleeding caused by uterine fibroids were selected. The main group of patients was divided into two subgroups: Group I A (20 women aged 28–33) received treatment with Esmya (ulipristal acetate 5 mg, manufactured by Gedeon Richter, Hungary) for a duration of 3 to 6 months, depending on the clinical picture and the woman’s reproductive plans. Group I B (20 women aged 34–39) were treated with the insertion of a levonorgestrel-releasing intrauterine system (Mirena). Group II (20 women aged 40–45) underwent hysteroscopic resection and ablation, followed by the insertion of the Mirena intrauterine system. Results. The analysis conducted revealed the positive outcomes associated with each method of treatment. Ulipristal acetate was shown to be preferable for younger women of reproductive age who have fertility plans, whereas hysteroscopic myomectomy and ablation followed by Mirena insertion were more effective for women in the premenopausal age group. Thus, the study confirms the importance of an individualized therapeutic approach based on age, reproductive intentions, and oncological risk.